General considerations for proteolytic cascades. (1st February 2004) - Amour, A.; Bird, M.; Chaudry, L.; Deadman, J.; Hayes, D.; Kay, C.
Abstract : Proteases are involved in the regulation of a wide variety of essential physiological processes, often by participating in a highly orchestrated sequence of events termed a 'proteolytic cascade'. Four major proteolytic cascades with disease relevance are candidates for therapeutic intervention, namely caspase-mediated apoptosis, blood coagulation, the matrix metalloproteinase cascade and the complement cascade. Understanding the various steps involved in the functioning of a cascade is key to deciding possible points of intervention for the design of potential drug molecules. This brief review illustrates some of the common features of proteolytic cascades using the blood coagulation pathway as an example.